Progress Towards Perennial Grains for Prairies and Plains. (March 2022) - Cassman, K.G.; Connor, D.J.
Perennial grain crops have been proposed as environmentally sustainable alternatives to annual grain crop systems that currently dominate the world's major breadbaskets. Proponents emphasize the potential of perennial grains to mimic natural systems and thereby reduce soil erosion, nutrient losses, and degradation of soil quality although need for adequate grain yield is also recognized as a prerequisite for success. Here we assess progress since 2005 (16 y) towards development of perennial grain systems with sufficient productivity to be seen as competent alternatives to annual wheat on the prairies and plains of North America and Australia. Based on reports published in refereed journals, we see little evidence that yield of Intermediate Wheatgrass or perennial wheats have improved to the point they are viable alternatives. Slow progress is attributed to lack of minimum grain yield targets for economic viability, lack of designated target regions where perennial grains are most likely to be competitive against annuals, selection methods that focused on components of yield rather than yield per se (i.e. on an area basis), and relatively small R & D investment compared to resources given to genetic and agronomic improvement of major annual grain crops. Given current status, we conclude that perennial grains will require substantial R & D investment and several decades if they are to achieve sufficient yield potential and yield persistence to become more than a niche crop for upscale health food markets in wealthy countries.